Connectedness to Nature and to Humanity: their association and personality correlates - Lee, Kibeom; Ashton, Michael C.; Choi, Julie; Zachariassen, Kayla (Frontiers in Psychology, 2015)
People differ in the extent to which they identify with humans beyond their ingroup and with non-human living things. We refer to the former as the Connectedness to Humanity (CH) and to the latter as the Connectedness to Nature (CN). In a sample of 324 undergraduate students, CH and CN were operationalized using the Identification with All Humanity Scale (McFarland, Webb, & Brown, 2012) and the Connectedness to Nature Scale (Mayer & Frantz, 2004), respectively. These variables correlated moderately with each other (r = .44) and shared Openness to Experience and Honesty-Humility as their primary personality correlates. CN was found to play an important role in mediating the relationships between the two personality variables and some specific pro-environmental/pro-animal attitudes and ecological behaviors.